Age related differences in balance approached by a novel dual-task test of anticipatory postural control strategies - Laessoe, Uffe; Larsen, Camilla Bille; Schunck, Line Noerkjaer; Lehmann, Line Jensen; Iversen, Halla (PloS one, 2019)
Assessment of balance is key to identifying individuals with postural control deficits and an increased fall risk. Subjects may compensate for their deficits by utilizing other strategies; to avoid this, it is recommended to assess postural control using a dual-task test. In most dual-task tests, it is difficult to monitor the performance in the secondary task and the individual's task prioritisation. This study evaluated a new dual-task testing approach. A convenience sample of 54 community-dwelling elderly (age 65+ years) and a reference group of 20 young participants were included in the study. They performed a test in which they could utilize cues to improve their baseline performance, provided their level of postural control allowed them residual attention capacity for this cognitive task. Significant performance differences were seen between the young and the elderly. The young group improved their performance time by 23.9% (10.7) and 7.1% (14.2) with a cue and a reverse cue, respectively, whereas the elderly failed to improve their performance time. The test was unable to distinguish between individuals within the elderly group due to a floor effect. The test reveals an individual's capacity to use cues for anticipatory postural control strategies in a dual-task setting and thereby estimates automatization of postural control. While the young subjects were capable of improving their performance during dual-task conditions, the elderly subjects apparently had no residual attentional capacity allowing them to utilize the facilitating cues. Within the elderly group, the dual-task aspects of the test added no value with respect to differentiation in the level of postural control.